Early integration of palliative care for outpatients with advanced cancer in general practice: how is the situation?—a cohort study - Engeser, Peter; Glassman, Joshua; Leutgeb, Rüdiger; Szecsenyi, Joachim; Laux, Gunter (Annals of palliative medicine, 2021)
Early integration of palliative care for outpatients with advanced cancer in general practice: how is the situation?—a cohort study
Gesehen am 09.06.2021